1988
DOI: 10.1111/j.1439-0507.1988.tb04416.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mammalian Steroid Hormones and Luteinizing Hormone on the Germination of Candida albicans and Implications for Vaginal Candidosis./;Die Wirkung von Säugersteroidhormonen und Gelbkörperreifungshormon auf die Keimschlauchbildung von Candida albicans und ihre Bedeutung für die Vaginalcandidose

Abstract: Summary:  Germination of Candida albicans was measured when blastospores were added to 10% rat serum and incubated for 2 h at 37°C. Sterols and steroids were tested for their ability to promote germination when added to serum. Oestriol, pregnanediol and pregnanetriol increased the percentage germination at concentrations of 0.001 — 1 μM. Luteinizing hormone similarly increased the percentage germination at concentrations of 0.001 — 1 μg/ml. 3‐isobutyl‐1‐methyl xanthine promoted germination at 1 — 100 μM. Zusam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 20 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…For instance, vulvovaginal candidiasis is a common ailment; an elevated level of estrogen and high glycogen content in vaginal secretions during pregnancy predispose women to the disease (46). Furthermore, 17-␤-estradiol could positively influence the germination of C. albicans (47,48). Interestingly, it was shown that the 17-␤-estradiol effect was brought about in a dose-dependent, as well as strain-dependent, manner (48).…”
Section: Cdr1p Transports Unconventional Moleculesmentioning
confidence: 99%
“…For instance, vulvovaginal candidiasis is a common ailment; an elevated level of estrogen and high glycogen content in vaginal secretions during pregnancy predispose women to the disease (46). Furthermore, 17-␤-estradiol could positively influence the germination of C. albicans (47,48). Interestingly, it was shown that the 17-␤-estradiol effect was brought about in a dose-dependent, as well as strain-dependent, manner (48).…”
Section: Cdr1p Transports Unconventional Moleculesmentioning
confidence: 99%
“…In addition, Candida undergoes the transition from blastospores to filaments in response to a wide variety of conditions, such as body temperature (37 °C), or the presence of some human hormones [42,43]. One of the strongest sets of filament-inducing conditions is the combination of body temperature (37 °C) and serum [44].…”
Section: Discussionmentioning
confidence: 99%
“…This transition to germ tubes may help Candida colonization [31][32][33][34]. Taken together, these data show that estradiol is capable of increasing the virulence of C. albicans, at least in part through modulation of its biofilm formation capabilities.…”
Section: Introductionmentioning
confidence: 97%
“…Another study shows that estrogen is the dominant hormone that supports and maintains experimental vaginal Candida infection, indicating that estrogen plays a role in C. albicans vaginitis [29,30]. Estrogen (17β-estradiol) also has a stimulatory effect on multiple morphologic phases having stimulatory effects on Coccidiodies immitis growth and increased the rate of spherule maturation and endospore release as well as functioning as an inducer of Candida germination by increasing the percentage of germination and germ tube length in a concentration specific manner [21,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%